A cost-effectiveness analysis of the 20-valent pneumococcal conjugate vaccine for the prevention of pneumococcal disease among Mexican adults aged ≥60 years - Jose Luis Huerta; An Ta; Elizabeth Vinand; Gustavo Ivan Torres; Warisa Wannaadisai; Liping Huang (Vaccine: X)
Current standard of care (SoC) for the prevention of pneumococcal disease among Mexican adults aged ≥60 years is a sequential regimen of pneumococcal conjugate vaccine (PCV) covering 13 serotypes (PCV13) followed by (→) 23-valent pneumococcal polysaccharide vaccine (PPSV23). This study estimated the effect of replacing the current SoC with a single dose of 20-valent PCV (PCV20) in the Mexican adult national immunization program (NIP).A probabilistic cohort model with a Markov framework was developed with an annual cycle to compare the cost-effectiveness of PCV20 versus SoC (PCV13 → PPSV23) from the Mexican public health sector perspective over a lifetime horizon. Costs and benefits were discounted at 5 % annually. Vaccine effectiveness was estimated from PCV13 clinical trial and PPSV23 effectiveness studies as well as the disease impact due to PCV13 → PPSV23 observed in Mexico. Other model inputs including epidemiology, costs, and utilities were sourced from Mexican-specific data. Uncertainty relating to model inputs was evaluated by deterministic and probabilistic sensitivity analyses as well as scenario assessments.PCV20 was estimated to be the dominant vaccination strategy versus SoC (PCV13 → PPSV23) in the Mexican adult population aged ≥60 years. PCV20 was associated with more clinical benefits and a cost saving of approximately 7 billion Mexican pesos compared with SoC at the population level. The results were shown to be robust in all sensitivity and scenario analyses.The replacement of the current SoC with PCV20 in the Mexican NIP is expected to simultaneously reduce the clinical burden of pneumococcal disease and associated medical costs among adults aged ≥60 years.